"Mamma mia! Autocorrection ruined my message": Interaction design challenges in a world of multilinguals - da Rosa, Diego Moreira; Guedes, Leandro Soares; Landoni, Monica; Silveira, Milene (Journal of the Brazilian Computer Society, 2026)
The widespread adoption of digital technologies and internet connectivity, particularly in developing regions, has drawn attention to the growing diversity of software users, who come from different cultural and linguistic backgrounds. Traditionally, human-computer interaction (HCI) research has treated language communities as static and isolated units, often equating them with national boundaries. However, linguistic research demonstrates that cultures are dynamic and interconnected, languages transcend borders, and people frequently speak two or more languages. To optimize HCI design, developers must account for these complex sociolinguistic realities, incorporating both social and individual dimensions of multilingualism. In this work, our aim is to contrast the demands of multilingual users with current design solutions. First, the behavior and difficulties of technology users in multilingual contexts were investigated through an online survey conducted with the academic communities of two universities: the Università della Svizzera italiana (USI), in Switzerland, and the Pontifical Catholic University of Rio Grande do Sul (PUCRS), in Brazil. Next, we present a pattern language that describes solutions aimed at multilingualism issues found in current websites and applications. In a final discussion, we compare the findings of the survey with the patterns, summarizing the challenges and opportunities for future research that aim to propose HCI design approaches with a focus on multilingualism.